An evaluation of and preference for variations of the Good Behavior Game with students with autism. (15th August 2020) - Vargo, Kristina; Brown, Christina
Abstract: The Good Behavior Game (GBG) has been implemented in numerous classrooms to decrease problem behavior. Despite the vast amount of literature, the effects of the inclusion of technology on disruptive behavior and student preference with students with autism have not been studied extensively. In this study, we compared the efficacy of the traditional GBG with technology‐enhanced GBG variations (ClassDoJo and ClassBadges) using a multielement design embedded within a reversal design with six male high school students diagnosed with autism. Results showed that all three GBG variations were similarly effective in decreasing disruptive behaviors. We then assessed individual preference for the GBG variations using a group‐oriented concurrent‐chains arrangement. All students demonstrated repeated preference for one GBG variation. These findings support the inclusion of technology‐enhanced GBG variations in special education classrooms with students with autism. Additionally, these results provide further evidence of the utility and applicability of the group‐oriented concurrent‐chains procedure.